Balancing Financial Viability and Public Value: An Economic–‎Accounting Appraisal of Academic Agribusiness Laboratories ‎in The Philippines - Perez, Gemar G.; Perez, April M.; Asi, Leonna Marrien U.; Arellano, Katherine T.; Abacan, Luzviminda A.; Verdadero, Joan Camille A. ‎; Perez, Jennifer M.; Mandane, Mary Grace T.; Ilagan, Amor A.; Amante, Albertson D.; Gamboa, Antonio A. ‎; Eje, Melmar D. (International Journal of Accounting and Economics Studies, 2025)
This study evaluates the potential of an academic livestock laboratory to transition into an academic–agribusiness enterprise by examining ‎market conditions, financial sustainability, and economic value creation. Analysis of household consumption patterns and retailer stocking ‎behavior across Lipa City, Batangas City, Taysan, and Lobo reveals consistent demand for processed pork products and persistent supply ‎gaps. The laboratory’s product lines—Filipino-style sausage, sweet cured pork, cured pork, and sweet pork stew—align well with consumer‎er preferences, indicating that local markets can absorb expanded production and that market demand provides a supportive environment for ‎enterprise development.‎Financial assessment shows that while the laboratory is capable of generating stable revenues, it faces difficulty achieving full cost recovery ‎using traditional accounting measures. Negative financial net present value, low internal rate of return, and an improving yet inadequate ‎operating self-sufficiency ratio highlight the structural constraints of academic laboratories. These facilities operate with high training costs, ‎intensive supervision, and process limitations that prevent full optimization for profit without compromising instructional and research functions.‎Economic evaluation offers a contrasting perspective. When non-market benefits—such as human-capital development, extension services, ‎consumer welfare gains from import substitution, local multiplier effects, and environmental offsets from biogas and fertilizer by-‎products—are incorporated, the project produces positive net benefits beginning in 2026. A positive economic net present value, a benefit–cost ratio above one, and a high economic internal rate of return indicate that societal benefits outweigh economic costs.‎To synthesize these findings, the study presents the Academic–Agribusiness Laboratory Leverage Conversion Model, framing such facilities as hybrid institutions. The model illustrates that financial limitations coexist with substantial economic value, supported by market de-‎mand and circular-resource practices. Overall, the laboratory’s sustainability is strengthened not through full commercialization but through ‎development-oriented operations backed by strategic subsidies and institutional support‎.
Keywords: Academic Laboratories; Cost Recovery; Economic Appraisal; Hybrid Enterprises; Public Value